The Effect of HDI and Unemployment Rate on Poverty in the Riau Islands - Azhar Suganda; Novi Ramadhini; Putri Nabila Harahap; Eko Wahyu Nugrahadi; Grace Gultom (Equity: Jurnal Ekonomi, 2024)
Poverty in the Riau Islands Province will be studied from 2018 to 2023 with a focus on how it affects HDI and unemployment rates. We analyzed secondary data obtained by the Central Statistics Agency (BPS) using quantitative methods in this research which uses a documentation approach. Random Effect Model (REM) was selected as the best estimation model after a series of panel data tests, including Chow, Hausman, and Legrange Multiplier tests. Unemployment has a significant and positive effect on poverty according to this research (coefficient = 3971.224). This means there is an increase of 39% in the underprivileged population for every 1% increase in the unemployment rate. There is a positive and statistically significant correlation between HDI and poverty (r=2086.092), which shows that a 1% increase in HDI means an increase in poverty of 20%. The findings from this study show increasing employment opportunities and improving the quality of human resources as potential efforts to reduce poverty in the Riau Islands Province.